Experimental and modeling studies of automotive-qualified OLEDs under electrical stress - Guney, Arda; Yelten, Mustafa Berke; Ferhanoglu, Onur; Kahraman, Nihan (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
In this paper, we aimed to investigate the reliability of an organic light-emitting diode (OLED) and propose a SPICE compatible electrical model for automotive exterior lighting applications. The proposed model smoothly provides the forward and reverse current-voltage relation and also dynamic capacitive behavior of OLED is included in the model. The Automotive Electronics Council-Qualified (AEC-Q) OLED samples that are currently used in a rear stop lamp have been electrically stressed with the current density of J = 11.5 mA/cm(2)(25% more than the nominal current density value) at room temperature. The model was presented through theoretical equations for forward and reverse current-voltage characteristics and impedance behavior of OLED. The simulated and experimental results are in close agreement with each other. We characterized the intrinsic capacitance, operational voltage, wavelength, and luminance variation of OLED aged under electrical stress for 7040 h. We utilized a simple setup to monitor variations in light intensity of the tested device with a CMOS camera. Under pure electrical stress, the dominant wavelength was slightly red-shifted by 3.29 nm, the threshold voltage of the OLED is increased from 4.2 V to 5.25 V, and luminance decayed to 88% of the initial luminance with stress time, whereas spectral shape was not affected.
Keywords: Aging; Automotive lighting; Electrical stress; Modeling; Reliability; Organic light-emitting diode (OLED); SPICE; LIGHT-EMITTING DEVICES; DEGRADATION MECHANISMS; DIODES; INJECTION; LIFETIME; CIRCUIT; Engineering; Science & Technology - Other Topics; Physics